Dissolved neodymium isotopes in the Mediterranean Sea. (1st April 2022) - Montagna, Paolo; Colin, Christophe; Frank, Martin; Störling, Tjördis; Tanhua, Toste; Rijkenberg, Micha J.A.; Taviani, Marco; Schroeder, Katrin; Chiggiato, Jacopo; Gao, Guohui; Dapoigny, Arnaud; Goldstein, Steven L.
Abstract: The neodymium isotopic composition (εNd ) of seawater is one of the most important geochemical tracers to investigate water mass provenance, which can also serve as a proxy to reconstruct past variations in ocean circulation. Nd isotopes have recently also been used to reconstruct past circulation changes in the Mediterranean Sea on different time scales. However, the modern seawater εNd dataset for the Mediterranean Sea, which these reconstructions are based on, is limited and up to now only 160 isotopic measurements are available for the entire basin. The lack of present-day data also limits our understanding of the processes controlling the Nd cycle and Nd isotopic distribution in this semi-enclosed basin. Here we present new εNd data from 24 depth profiles covering all Mediterranean sub-basins, which significantly increases the available dataset in the Mediterranean Sea. The main goal of our study is to better characterize the relationship between the dissolved Nd isotope distributions and major water masses in the Mediterranean Sea and to investigate the impact and relative importance of local non-conservative modifications, which include input of riverine particles and waters, aeolian-derived material and exchange with the sediments at continental margins. This comprehensive εNd dataset reveals a clear εNd – salinity correlation and a zonal and depth gradient with εNd systematically increasing from the western to the eastern Mediterranean basin (average εNd  = −8.8 ± 0.8 and −6.7 ± 1 for the entire water column, respectively), reflecting the large-scale basin circulation. We have evaluated the conservative εNd behaviour in the Mediterranean Sea and quantified the non-conservative components of the εNd signatures by applying an Optimum Multiparameter (OMP) analysis and results from the Parametric Optimum Multiparameter (POMP) analysis of Jullion et al. (2017). The results of the present study combined with previously published Nd isotope values indicate that dissolved εNd behaves overall conservatively in the open Mediterranean Sea and show that its water masses are clearly distinguishable by their Nd isotope signature. However, misfits between measured and OMP- and POMP-derived εNd values exist in almost all sub-basins, especially in the eastern Levantine Basin and Alboran Sea at intermediate-deep depths, which can be explained by the influence of detrital lithogenic εNd signatures through interaction with highly radiogenic Nile sourced volcanic fractions and unradiogenic sediments, respectively. The radiogenic signature acquired in the eastern Levantine Basin is carried by the Levantine Intermediate Water and transferred conservatively to the entire Mediterranean at intermediate depths. Our measured εNd values and OMP- and POMP-derived results indicate that non-conservative contributions originating from sediment sources are then propagated by water mass circulation (with distinct preformed εNd ) along the Mediterranean Sea through advection and conservative mixing. Mediterranean εNd effectively traces the mixing between the different water masses in this semi-enclosed basin and is a suitable water mass tracer.